Chewing Doma (Fermented Betel Nut): Culture versus Cancer? - Patel, Amol; Patel, Manali; Tshering, Phub; Koyyala, Venkata Pradeep Babu; Ghadyalpatil, Nikhil (South Asian Journal of Cancer, 2023)
Areca nut consumption is embedded in many cultures, including that of Bhutan, several parts of India, and other South Eastern countries. Traditional fermenting of areca nut results in the production of what is called doma in Bhutan. The process enhances its carcinogenic potential and is tightly linked to oral and upper gastrointestinal cancers. As many as 45% of Bhutanese people chew doma. It is the number one cause of cancers of the oral cavity, oropharynx, hypopharynx, and larynx. We propose the slogan “Don't chew your way to cancer, say no to doma” would help in reducing oral and esophageal cancers in Bhutan.
Keywords: carcinogenic; lifestyle; India; Bhutan; chewing; areca